CHANGES IN LUNG FUNCTION IN THE TREATMENT OF PATIENTS WITH EXOGENOUS ALLERGIC ALVEOLITIS - V. B. Nefedov; L. A. Popova; E. A. Shergina; N. N. Makaryants (Туберкулез и болезни лёгких, 2014)
Total lung capacity (TLC), lung capacity (LC), forced LC (FLC), intrathoracic volume (ITV), pulmonary residual volume (PRV), forced expiratory volume in one second (FEV1 ), (FEV1 )/LC%, peak expiratory flow (PEF), maximum expiratory flow rate (MEFR)25, MEFR50, MEFR75, Raw, Rin, Rex, DLCO-SB, DLCO-SB/VА, РаО2 , and РаСО2 were determined in 43 patients with exogenous allergic alveolitis (EAA) before, during, and after treatment with glucocorticosteroids, hemapheresis, ambroxol, and fluimucil. Lung function became better in more than half (53.5%) of the patients and worse in one fourth (25.6%); a combination of positive and negative functional changes was detected in 14.0%. Improved lung function was noted in 75.0, 50.0, and 38.5% of the patients with acute, subacute, and chronic EAA, respectively. Deterioration of lung function was determined in 46.2, 22.2, and 8.3% of the patients with chronic, subacute, and acute alveolitis, respectively. Better lung function manifested itself mainly as positive changes in lung volumes and capacities and pulmonary gas exchange function, less frequently as improved bronchial patency in the patients with acute and subacute EAA whereas the rate of positive functional changes in lung volumes and capacities, bronchial patency, and pulmonary gas exchange function was equal in those with chronic EAA. Poorer lung function appeared as negative changes in lung volumes and capacities in the patients with acute EAA, as worse pulmonary gas exchange function and negative changes in lung volumes and capacities and deteriorated bronchial patency in those with subacute and chronic EAA.